From Petri Nets to Graph Transformation Systems - Baldan, Paolo; Corradini, Andrea; Gadducci, Fabio; Montanari, Ugo (Electronic Communications of the EASST, 2010)
Hans-Joerg Kreowski was among the first researchers to point out that Place/Transition Petri nets can be interpreted as instances of Graph Transformation Systems, a fact now considered folklore. We elaborate on this observation, discussing how several different models of Petri nets can be encoded faithfully into Graph Transformation Systems. The key idea we pursue is that the net encoding is uniquely determined, and distinct net models are mapped to alternative approaches to graph transformation.